Aspects of modern language teaching in Europe - Gewehr, Wolf; Catsimali, Georgia (Taylor & Francis, 1998)
In this book teaching experience and research from practitioners in four European countries throw new light on old problems faced every day, while other reveal innovative teaching methods and insights into how teachers and learners interact.